PEMANFAATAN UAP KELUARAN EVAPORATOR UNTUK PENGERINGAN AMPAS TEBU BAHAN BAKAR PABRIK GULA - Azrul Syamsu; Nurul Hidayati Fithriyah; Ratri Ariatmi Nugrahani (Jurnal Teknologi, 2023)
Have been factors that influence on the use of the baggase as fuel. One of them is water contained in the baggase. A sugar factory in Lampung Tengah district is PT Gula Putih Mataram, produce baggase in contained water by 50,10%. The purpose of this research is to know the number of water to levels unloaded on baggase by using heat from steam exodus evaporator. know influence the flow hot air to the water level of optimal for flow of steam exodus evaporator, used to draining bagasse. Know time drying to influence the water level and time best of process of drying bagasse, use of heat from the exodus steam evaporator. And the research methodology used data processing. Where data is collected of direct observation in PT Gula Putih Mataram, and study literature in the form data of a journal before. Using a hot vapor exodus evaporator in heat exchanger, rate obtained hot air flow 36.296,62 kg/hours, with 40Â°C temperature. Next hot air is used as air dryer in rotary dryer. Air dryer to flow of 32 tons/hours, 33 tons/hours, 34 tons/hours, 35 tons/hours and 36 tons/hours, obtained the the water level of 45,05%; 44,89%; 44,73%; 44,58% and 44,42%. With sample 36 tons/hours take 5 sample drying time. That is 1 hours, 2 hours, 3 hours, 4 hours and 5 hours, and is found the water levels by 44,42%; 38,74%; 33,06 %; 27,38% and 21,70%. Of the results of data processing shows variations in the drying time flow hot air and give a linear variation to the moisture content of reduced the number. Where the bigger the flow air dryer will increase the moisture content of which can be reduced. And time for drying, the longer the drying hence the larger the to amount to the moisture content of which can be reduced.